2018
DOI: 10.1016/j.abrep.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between concussion and alcohol consumption among university athletes

Abstract: IntroductionThis study investigated concussion as a potential risk factor for increased alcohol consumption in university athletes.MethodsUsing a cross-sectional design, 41 university students (37% with a history of concussion) completed self-report measures, while electrodermal activation (EDA) was recorded for each participant to capture baseline physiological arousal.ResultsAs expected, concussion status significantly predicted alcohol consumption over and above athletic status, b = 0.34, p = 0.034, 95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…Importantly, when investigating potential mechanisms of this relationship, it was found that physiological arousal was a partial mediator of the relationship between injury severity and physical aggression, such that those with more severe injuries exhibited lower levels of physiological arousal, which in turn accounted for higher levels of aggression. Consistent with previous work indicating physiological dysregulation after concussion (e.g., Alcock et al., 2018; Baker & Good, 2014; van Noordt & Good, 2011), these findings imply that aggressive behaviors may be associated with concussion history (i.e., physiological underarousal), over and above athletic status, due to physiological unpreparedness. Alternatively, due to their chronically underaroused state, these athletes may be more likely to engage in aggressive forms of play in an attempt to increase their baseline levels of alertness; however, the current study did not directly test these potential explanations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Importantly, when investigating potential mechanisms of this relationship, it was found that physiological arousal was a partial mediator of the relationship between injury severity and physical aggression, such that those with more severe injuries exhibited lower levels of physiological arousal, which in turn accounted for higher levels of aggression. Consistent with previous work indicating physiological dysregulation after concussion (e.g., Alcock et al., 2018; Baker & Good, 2014; van Noordt & Good, 2011), these findings imply that aggressive behaviors may be associated with concussion history (i.e., physiological underarousal), over and above athletic status, due to physiological unpreparedness. Alternatively, due to their chronically underaroused state, these athletes may be more likely to engage in aggressive forms of play in an attempt to increase their baseline levels of alertness; however, the current study did not directly test these potential explanations.…”
Section: Discussionmentioning
confidence: 95%
“…The vmPFC's location proximal to the orbital bones of the skull (Morales, Diaz‐Daza, Hlatky, & Hayman, 2007) renders it more susceptible to disruption following rapid acceleration/deceleration of the head; as a result, attenuated arousal is experienced across the spectrum of injury severity (Iverson & Lange, 2009)—even after milder injuries (Alcock, Gallant, & Good, 2018; Baker & Good, 2014; van Noordt & Good, 2011). Physiological underarousal, indexed by dampened respiration, electrodermal activation (EDA), and heart rate (Craig, 1968; Lazarus, Speisman, & Mordkoff, 1963), has been proposed as a mechanism of impulsivity and risk‐taking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Concussion history has also been associated with higher alcohol and cannabis use in college students [ 29 ]. Athletes are at greater risk for concussion [ 30 ], and prior research has suggested that higher exposure to repetitive head injuries is associated with increased substance use [ 31 ] and symptoms of depression [ 32 , 33 ]. Higher exposure to repetitive head impacts has been suggested to affect vulnerable brain areas involved in impulsive and risk-taking behaviours, which may account for increased substance use [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Athletes are at greater risk for concussion [ 30 ], and prior research has suggested that higher exposure to repetitive head injuries is associated with increased substance use [ 31 ] and symptoms of depression [ 32 , 33 ]. Higher exposure to repetitive head impacts has been suggested to affect vulnerable brain areas involved in impulsive and risk-taking behaviours, which may account for increased substance use [ 31 ]. Within our limited sample size, we did not observe differences in concussion history between substance users and non-user; however, the relationship between cannabis use and symptom endorsement in athletes requires further investigation to explore whether associations between substance use and mental health status are mediated by concussion history.…”
Section: Discussionmentioning
confidence: 99%
“…Research on concussions has increased due to their associated adverse health outcomes. In particular, concussions are associated with reduced academic performance (Wasserman et al, 2016), mental health problems, including depression, anxiety (Martin & Chaney, 2018;Rice et al, 2018) and aggression (Mosti & Coccaro, 2018;Rice et al, 2018), hazardous alcohol use (Alcock et al, 2018;Martin & Chaney, 2018) and cognitive impairment (Karr et al, 2014). Although research on concussions commonly focuses on athletic participation (Bryan et al, 2016;Covassin et al, 2018;Manley et al, 2017;Marshall et al, 2015;Prien et al, 2018), particularly among college athletes (Baugh & Kroshus, 2016;Dompier et al, 2015;Kerr et al, 2016), little research has been conducted to investigate the association between diverse forms of interpersonal violence victimisation (e.g., emotional abuse, physical abuse and sexual assault) and concussions particularly among college students.…”
Section: Introductionmentioning
confidence: 99%